THE RELEVANCE OF HIGH SPIRITUALITY IN THE PERIOD OF GLOBAL CRISES - Ruzimurod Pulatov (Web of Journals Publishing, 2024)
The root causes of any crisis, in general, stem from spirituality, spiritual crises. Therefore, to overcome all social crises in human life, it is necessary to develop spirituality and cultivate high spirituality in society. This indicates the importance of studying this issue within a separate topic.
Keywords: Crisis, global crisis, spiritual crisis, causes of global crises, factors for overcoming crises, spirituality, high spirituality.